Quantitative sub-surface and non-contact imaging using scanning microwave microscopy. (9th March 2015) - Gramse, Georg; Brinciotti, Enrico; Lucibello, Andrea; Patil, Samadhan B.; Kasper, Manuel; Rankl, Christian; Giridharagopal, Rajiv; Hinterdorfer, Peter; Marcelli, Romolo; Kienberger, Ferry
Abstract: The capability of scanning microwave microscopy for calibrated sub-surface and non-contact capacitance imaging of silicon (Si) samples is quantitatively studied at broadband frequencies ranging from 1 to 20 GHz. Calibrated capacitance images of flat Si test samples with varying dopant density (10 15 –10 19 atoms cm −3 ) and covered with dielectric thin films of SiO2 (100–400 nm thickness) are measured to demonstrate the sensitivity of scanning microwave microscopy (SMM) for sub-surface imaging. Using standard SMM imaging conditions the dopant areas could still be sensed under a 400 nm thick oxide layer. Non-contact SMM imaging in lift-mode and constant height mode is quantitatively demonstrated on a 50 nm thick SiO2 test pad. The differences between non-contact and contact mode capacitances are studied with respect to the main parameters influencing the imaging contrast, namely the probe tip diameter and the tip–sample distance. Finite element modelling was used to further analyse the influence of the tip radius and the tip–sample distance on the SMM sensitivity. The understanding of how the two key parameters determine the SMM sensitivity and quantitative capacitances represents an important step towards its routine application for non-contact and sub-surface imaging.